2008
DOI: 10.1007/s11010-008-9929-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent role of Akt and ERK activation in cardioprotective effect of Ca2+ channel- and beta-adrenergic receptor blockers

Abstract: We studied cardioprotective as well as Akt and extracellular signal-activated kinase (ERK) activating effect of a Ca(2+) antagonist and a beta-adrenergic receptor blocker during ischemia-reperfusion, and compared these properties of the substances with that of a poly(ADP-ribose) polymerase (PARP) inhibitor used as a positive control throughout the experiments. Langendorff-perfused isolated rat hearts were subjected to 25 min global ischemia followed by 45 min reperfusion, and recovery of energy metabolism as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Using Western blot analysis, we found that the ERK1/2 phophsrylations of threonines at 202 th and tyrosine at 204 th sites were enhanced after TAC surgery, compared with control(Fig 4A and 4C, P< 0.001). Moreover, the phosphorylations of threonines at 202th and tyrosine at 204th sites were reduced after metoprolol incubation, consistent with published data [14] . Interestingly, the phosphorylations of ERK1/2 was blocked after SalB stimulation(P<0.001, Fig 4A and 4C).…”
Section: Resultssupporting
confidence: 92%
“…Using Western blot analysis, we found that the ERK1/2 phophsrylations of threonines at 202 th and tyrosine at 204 th sites were enhanced after TAC surgery, compared with control(Fig 4A and 4C, P< 0.001). Moreover, the phosphorylations of threonines at 202th and tyrosine at 204th sites were reduced after metoprolol incubation, consistent with published data [14] . Interestingly, the phosphorylations of ERK1/2 was blocked after SalB stimulation(P<0.001, Fig 4A and 4C).…”
Section: Resultssupporting
confidence: 92%
“…Various experimental data demonstrated the beneficial role of this drug class in different heart diseases. In vitro data implicated the activation of pro-survival pathways as a mechanism mediating the cardioprotective effects of calcium blockers (52). Treatment with verapamil improved the redox state in a model of ischemia-reperfusion injury.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Treatment with verapamil improved the redox state in a model of ischemia-reperfusion injury. Furthermore, verapamil induced the activation of Akt and ERK1/2 pathways, leading to a number of cardioprotective effects, such as the downregulation of apoptotic pathways (52). It was also proposed that this may be a mechanism by which calcium blockers amplify the ROS-induced damage, though a direct association between ROS and cardioprotective mechanisms of calcium channels blockers is not clearly demonstrated (52).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although currently considered of major interest for drug development (Azzi et al, 2003;Kenakin, 2005;Whalen et al, 2011), the clinical significance of biased agonism is poorly understood. It is however clear that activation of ERK is cardioprotective during ischemia (Lips et al, 2004;Rose et al, 2010) and contributes to the cardioprotective actions of b-adrenergic antagonists (Kovacs et al, 2009).…”
Section: Comparison Of Landiolol and Esmololmentioning
confidence: 99%